the power of habit : why we do what we so and how to change - Duhigg, charles; Charles Duhigg (United Kingdom Paperback, 2012)
The Power of Habit by Charles Duhigg explains that habits are not destiny, but rather neurological loops consisting of a cue, routine, and reward. By identifying the cue and reward, individuals can change the routine$1 (Bthe behavior$1 (Bto transform habits. Key takeaways include understanding "keystone habits" that trigger widespread change and the necessity of belief in the change process. s
English